Analisis Kesalahan Berbahasa Indonesia dalam Whatsapp Mahasiswa Fakultas Ilmu Kesehatan Program Studi Farmasi Angkatan 2023 dengan Dosen MKDU Universitas dr. Soebandi - Setyorini Dwi Agustini; Siti Yuliana; Hamliyah Hamliyah (Universitas Muhammadiyah Jember, 2024)
Whatsapp is always used in communication at this time. Lecturers and students also use the application to communicate about lectures. However, there are still many mistakes in writing messages in whatsapp. The objectives of this study are 1) To describe and explain capitalization errors, 2) Describe and explain the forms of errors in writing punctuation dots (.), commas (,), question (?), exclamation points (!), colons (:), quotation marks (